Estudio Estadístico De Lacaracterización De Residuos Solidos De La Parroquia Taracoa Provincia De Orellana - Juan Pablo Wayllas Pazmiño (European Scientific Journal, ESJ, 2018)
In this study, a statistical analysis was carried out on the management of solid household waste generated in the Taracoa parish of the province of Orellana in the Ecuadorian Oriente. The inhabitants of the study community must, however, observe the legal regulations provided by the municipality of Orellana. The analysis was aimed at identifying the per capita production of solid waste and the characterization of them. 61 families were chosen to carry out the study, with an average of 5 inhabitants for each of them, resulting in a total of 305 inhabitants. The methodology of this study uses the probabilistic method to obtain the samples. These samples were taken directly from the houses identified for sampling. The results show that the solid waste PPC in the parish Taracoa of the province of Orellana was 0.89 kg/hab/day, generating a total of 273.60 kg/day. This, therefore, was sent to the dump of the municipality of Orellana. The statistical analysis determines that in the domiciles of the parish Taracoa of the province of Orellana, organic waste occupies the first place with 75.60%. This was followed by plastic sleeves with 8.60%, plastic bottles with 5.20%, carton with 4.90%, paper with 3.95%, and cans with 1.75%.